Recent advances in municipal landfill leachate: A review focusing on its characteristics, treatment, and toxicity assessment - Luo, Hongwei; Zeng, Yifeng; Cheng, Ying; He, Dongqin; Pan, Xiangliang (The Science of the total environment, 2020)
Nowadays, sanitary landfilling is the most common approach to eliminate municipal solid waste, but a major drawback is the generation of heavily polluted leachates. These leachates must be appropriately treated before being discharged into the environment. Generally, the leachate characteristics such as COD, BOD/COD ratio, and landfill age are necessary determinants for selection of suitable treatment technologies. Rapid, sensitive and cost-effective bioassays are required to evaluate the toxicity of leachate before and after the treatment. This review summarizes extensive studies on leachate treatment methods and leachate toxicity assessment. It is found that individual biological or physical-chemical treatment is unable to meet strict effluent guidelines, whereas a combination of biological and physical-chemical treatments can achieve satisfactory removal efficiencies of both COD and ammonia nitrogen. In order to assess the toxic effects of leachate on different trophic organisms, we need to develop an appropriate matrix of bioassays based on their sensitivity to various toxicants and a multispecies approach using organisms representing different trophic levels. In this regard, a reduction in toxicity of the treated leachate will contribute to assessing the effectiveness of a specific remediation strategy. [Display omitted] •Suitable treatment technologies depend mainly on leachate COD, BOD/COD ratio, and landfill age.•Efficiencies, cost and environmental impacts are three major criteria for selecting treatment technologies.•A combination of two or more treatment technologies can achieve satisfactory removal efficiencies.•An appropriate matrix of bioassays should be developed to assess the toxic effects of leachate.